Space-time coordination dynamics in basketball: Intra- and inter-couplings amongst player dyads - Bourbousson, J.; Seve, C.; McGarry, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Interpersonal coordination in game sports is an emerging field of interest in sport science. Indeed, formal evidence is gathering for the viability of a complex system description for some individual sports but not yet for team sports. The objective of the present study therefore was to assess basketball game behaviour within the general context of a dynamical system description. Methods Six game sequences from a French professional basketball game were analysed from which the x-y coordinate data of each player was obtained using a tracking procedure. The longitudinal (forward-backward movements) and lateral (side-to-side movements) patterns of each possible dyad were then subjected to relative phase analysis using the Hilbert transform. The relative phases were reported as frequency histogram data. Single instances from select dyads and game sequences were then investigated for evidences of stabilities and instabilities as well as phase transitions within a data sequence. Results In general the attacker-defender dyads demonstrated a strong in-phase relation (attractor of 0 degree) for the longitudinal and lateral data. In the lateral direction, however, for both teams the two wing players being teammates yielded strong attractions to anti-phase (attractor of 180 degrees), and the guard and center players demonstrated a bi-modal distribution with phase attractors of -150 degrees and 90 degrees. Discriminating the two teams, one team exhibited more distinct intra-coupling phase relations than the other. Single instances from select dyads and game sequences furthermore demonstrated evidences of phase stabilities (on 0 degree and 180 degrees) that were temporarily perturbed before the phase relation was restored. Intermittent switching was also observed in the data either between in-phase and three quarter-phase, or between the anti-phase and quarter-phase relations. Discussion The results demonstrated that the forward-backward movements of basketball players are much constrained by the context of the game demands. This finding was not extended to the lateral direction, however, as evidenced in the varying phase relations reported for some dyads. Similar patterns across teams were identified suggesting the presence of a common coupling within the dyads based on position considerations, a possible consequence of well established game playing habits. That said, some observed differences between the teams indicated that one team was more patterned in its behaviours whereas the other was more changeable to the game context. In sum, the findings demonstrated that the space-time patterns of basketball player dyads conform to a uniform description according to dynamical principles of self-organizing systems.